Black male student teachers: tomorrow's teachers?. Issue 2 (11th June 2018) - Maylor, Uvanney
Abstract : Purpose: This paper aims to understand the preparation that a group of black male pre-service students received during their course and its impact on their willingness to commit to entering the teaching profession. Design/methodology/approach: The paper draws on findings from a small-scale qualitative study of black and minority ethnic student teachers' experiences in one initial teacher education institution. Findings: The paper raises questions as to whether black pre-service teachers' experiences of a lack of acceptance in schools during their pre-service training contribute to the under-representation of black male teachers in English schools. Originality/value: There is limited research on the experiences of black male student teachers. The paper brings new insights and offers reasons for black male student teachers not entering the teaching profession.